Using fetal-heart size measured from ultrasound scanner images to estimate age of gestation in goat - Abdullah, Ramli; Khadijah, W.E.W.; Airina, R.; Nizam, A.R.M. (2011)
The necessity in detecting pregnancy particularly estimating the gestation period in. goat is undeniable. This objectives of this study were to observe images of fetus and fetal-related images in goats throughout pregnancy period, to test the reliability of fetal counting using Real-time B mode ultrasound, to measure and then to compare the development of fetal heart size in both single and twin pregnancies, to compare the changes in heart echogenicity in both single and twin pregnancies in does and to estimate the accuracy of pregnancy detection as well as age related pregnancy structures using ultrasonography. Structures were detected during gestation period including sac, fetus, fetal heart, amniotic fluid, uterine wall, ribs, spinal cord, fetal organ and placentomes. Changes in fetal heart echogenicity and area throughout both single and twin pregnancy were determined and evaluated using ultrasound scanning. Equations to estimate age of gestation were derived from polynomial and linear regression between gestational age and heart area in does for single and twin pregnancies. Blind test was conducted on polynomial and linear relationships between heart area size and gestational age. For polynomial relationship, 65, 69 and 92% of pregnant does delivered within +/- 1, +/- 2 and +/- 3 weeks of the delivery dates, respectively. Meanwhile, linear relationship gave 62, 69 and 77%, respectively. In conclusion, sonographic fetometry of fetal heart size is reliable to estimate the age of gestation in goat.